Implementation of the Framework for the Application System Thinking (FAST) Method on the Management Information System of the Al-Ittihad Mosque - Ronny Ramadhan Hasibuan; Samsudin (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
The purpose of this research is to implement the FAST (Framework for The Aplication System Thingking) method on the mosque management information system. And to build and design a mosque management information system by applying the FAST (Framework for The Aplication System Thingking) method for decision making in the reminder system. The results of the study concluded that the existence of this Mosque Management Information system can help activities in the mosque, this system can manage the rental process, khatib reminders, information on BKM activities and the BKM can easily manage activities and make it easier for the community to get information and will save more time and costs, so that what is needed by the community will be better.